Morphological variability the populus diversifolia schrenk. in natural populations of the desert of mangistau (Eurasian Journal of Ecology, 2016)
Results of studying of intraspecific variability Populus diversifolia Schrenk. on the example of 6 morfologo-biometric indicators of growth (height, diameter of a circle of krone and a trunk, length, width and quantity of cloves on a sheet plate) are given on the basis of which the conclusion about a high polimorfical and ecological plasticity of this rare species in the conditions of a desert zone of Mangistau area are drawn.
Keywords: Populus diversifolia; population; variability; ecotype; height; diameter